The land: Primary category of faith - Volschenk, G. J. (HTS teologiese studies, 2004)
This review article of Walter Brueggemann’s book “The land: Place as gift, promise, and challenge in biblical faith” (2002) mainly focuses on land as the primary category of faith in the Bible. The main focus is on the dialectical interrelationship between land possession and land-loss. A holistic, systemic and triangular interrelationship exists between God, land, Israel and Torah/covenant. The balance in this triangular relationship is essential for equilibrium in the system. The pendulum thus swings between land, exile and kingdom or in other words, between “landedness” and “landlessness”. The conclusion is that ignorance of this holistic and triangular interrelationship is of great cost and peril to any generation’s perspective on land.